Extraction of Prosody for Automatic Speaker, Language, Emotion and Speech Recognition - Mary, Leena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This updated book expands upon prosody for recognition applications of speech processing. It includes importance of prosody for speech processing applications; builds on why prosody needs to be incorporated in speech processing applications; and presents methods for extraction and representation of prosody for applications such as speaker recognition, language recognition and speech recognition. The updated book also includes information on the significance of prosody for emotion recognition and various prosody-based approaches for automatic emotion recognition from speech.
Introduction -- Signiﬁcance of Prosody for Speaker, Language, Emotion and Speech Recognition -- Automatic Extraction of Prosody for Speaker, Language, Emotion and Speech Recognition -- Modeling and Fusion of Prosody for Speaker, Language, Emotion and Speech Recognition -- Conclusion.
Keywords: Signal processing; Computational linguistics; Natural language processing (Computer science).; Signal, Speech and Image Processing; Computational Linguistics; Natural Language Processing (NLP).